2003
DOI: 10.1007/s00192-003-1106-8
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of urinary, fecal and double incontinence in the elderly living at home

Abstract: The aim of this study was to evaluate the prevalence of urinary, fecal and double incontinence in the elderly, through a population-based cross-sectional survey. The study included all patients aged 60 and over of nine general practices in the Nijmegen Monitoring Project. Patients living in a home for the elderly were excluded, as well as patients with dementia, patients who were too ill to participate and patients with a catheter. There were 5278 selected patients who received a postal questionnaire. Of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(35 citation statements)
references
References 22 publications
6
26
1
Order By: Relevance
“…The US National Health and Nutrition Examination Survey (NHANES) of 2005–2006 found no significant difference in FI between women and men (8.9% vs. 7.7%, p = 0.31) [24]. This was also found in other US studies [2,25], as well as studies for Netherlands [26] and Korea [17]. A study done in Japan among the elderly showed higher prevalence among the women [14].…”
Section: Discussionsupporting
confidence: 63%
“…The US National Health and Nutrition Examination Survey (NHANES) of 2005–2006 found no significant difference in FI between women and men (8.9% vs. 7.7%, p = 0.31) [24]. This was also found in other US studies [2,25], as well as studies for Netherlands [26] and Korea [17]. A study done in Japan among the elderly showed higher prevalence among the women [14].…”
Section: Discussionsupporting
confidence: 63%
“…The most prevalent type of UI was stress UI (SUI), ranging from 13 to 50% [7,11] in the former group of analyzed studies [8] and from 6.4 to 42.2% [9,12] in the latter. The number of women included in the former group ranged from 405 [13] to 27,936 [11] and in the latter from 227 to 142,651 [14,15]. Study populations came from population-based, cross-sectional surveys carried out in the following European countries: Austria, Denmark, Finland, France, Germany, Greece, Italy, Norway, Portugal, Spain, Sweden, The Netherlands, UK and Turkey.…”
Section: Resultsmentioning
confidence: 99%
“…FI can lead to loss of patients' selfesteem and diminished quality of life [3]. Recent evidence has shown little difference in FI incidence between males and females challenging the traditional theory of "stretching of the pelvic floor" during childbirth resulting in female predominance [4][5][6][7]. In most patients, FI can be attributed to more than one causative factors.…”
Section: Introductionmentioning
confidence: 98%